2006
DOI: 10.1523/jneurosci.3903-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of Vestibular Otolith Afferents after Ototoxic Damage

Abstract: Regeneration of receptor cells and subsequent functional recovery after damage in the auditory and vestibular systems of many vertebrates is well known. Spontaneous regeneration of mammalian hair cells does not occur. However, recent approaches provide hope for similar restoration of hearing and balance in humans after loss. Newly regenerated hair cells receive afferent terminal contacts, yet nothing is known about how reinnervation progresses or whether regenerated afferents finally develop normal termination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
51
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 70 publications
(103 reference statements)
8
51
0
Order By: Relevance
“…In the vestibular organs, regenerated hair cells reacquire the same orientations and physiological sensitivities as their counterparts in the undamaged ear (Dye et al 1999;Zakir and Dickman 2006), but the molecular signals that regulate hair cell structure and orientation during regeneration are not known. Recent developmental studies of the mammalian ear have demonstrated that molecules of the planar cell polarity (PCP) pathway play a critical role in the establishment of hair cell orientation (Montcouquiol et al , 2006aWang et al 2006;Deans et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In the vestibular organs, regenerated hair cells reacquire the same orientations and physiological sensitivities as their counterparts in the undamaged ear (Dye et al 1999;Zakir and Dickman 2006), but the molecular signals that regulate hair cell structure and orientation during regeneration are not known. Recent developmental studies of the mammalian ear have demonstrated that molecules of the planar cell polarity (PCP) pathway play a critical role in the establishment of hair cell orientation (Montcouquiol et al , 2006aWang et al 2006;Deans et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…There have been surprisingly few studies of the afferent innervation of regenerated hair cells (Duckert and Rubel, 1990;Duckert and Rubel, 1993;Haque et al, 2009;Ryals and Westbrook, 1994;Xiang et al, 2000;Zakir and Dickman, 2006). New synaptic endings are seen on repairing and regenerating hair cells soon after their appearance, but normal innervation is not restored for much longer periods (Haque et al, 2009;Ryals and Westbrook, 1994;Whitlon and Sobkowicz, 1991;Zakir and Dickman, 2006).…”
Section: Research Articlementioning
confidence: 99%
“…New synaptic endings are seen on repairing and regenerating hair cells soon after their appearance, but normal innervation is not restored for much longer periods (Haque et al, 2009;Ryals and Westbrook, 1994;Whitlon and Sobkowicz, 1991;Zakir and Dickman, 2006). Rapid functional recovery after sound trauma may be associated with processes involving the surviving hair cells -rather than with the regeneration of lost hair cells (Reng et al, 2001).…”
Section: Research Articlementioning
confidence: 99%
“…We then directly characterized the functional recovery of gaze stability during vestibular regeneration based on our previously established morphologic landmarks of receptor recovery (Dickman and Lim 2004;Dye et al 1999;Zakir and Dickman 2006). Finally, we demonstrate links between component mechanisms of gaze stability and vestibular receptor function in birds.…”
Section: Introductionmentioning
confidence: 96%
“…In birds, reptiles, and amphibians, the occurrence of spontaneous regeneration of vestibular receptors following inner ear damage is now well established (Corwin and Cotanche 1988;Cruz et al 1987;Weisleder and Rubel 1993). Although much of the inner ear morphology returns to normal phenotypic patterns (reviewed in Matsui et al 2005), significant differences persist in vestibular afferent innervation following complete regeneration (Zakir and Dickman 2006). The effects of vestibular receptor loss on the central neuronal processing of motion information that govern gaze and postural stability are not yet fully understood.…”
Section: Introductionmentioning
confidence: 99%